(untitled) (Third Sector Social Economic Review, 2019)
Remittances, which tend to increase continuously in the world, affect the economies which accept high remittances in many ways. Therefore, many studies have been put forward regarding the macroeconomic effects of remittances. In this study, the impact of remittances on economic growth is analyzed by ARDL bounds testing approach for the period of 1974-2018 in Turkey. According to the findings, remittances haven’t a statistically significant effect on economic growth in the long run. The most important factor in this finding is the declining trend of remittances in the Turkish economy. Although remittances have increased around the world, the share of remittances in the Turkish GDP is quite low.